Enhanced expression of NLRP3 inflammasome components by monocytes of patients with pulmonary paracoccidioidomycosis is associated with smoking and intracellular hypoxemia - Amorim, Barbara Casella [UNESP]; Pereira-Latini, Ana Carla; Golim, Marjorie de Assis [UNESP]; Ruiz Júnior, Raul Lopes [UNESP]; Yoo, Hugo Hyung Bok [UNESP]; Arruda, Maria Sueli Parreira de [UNESP]; Tavares, Aldo Henrique; Cavalcante, Ricardo de Souza [UNESP]; Mendes, Rinaldo Poncio [UNESP]; Pontillo, Alessandra; Venturini, James [UNESP] (Elsevier, 2020)
Paracoccidioidomycosis (PCM) is a systemic mycosis caused by thermally dimorphic fungi of the genus Paracoccidioides that affects predominantly 30-60-year-old male rural workers. The main clinical forms of the disease are acute/subacute, chronic (CF); almost all CF patients develop pulmonary fibrosis, and they also exhibit emphysema due to smoke. An important cytokine in this context, IL-1β, different from the others, is produced by an intracellular multimolecular complex called inflammasome that is activated by pathogens and/or host signs of damage. Inflammasome has been recognized for its contribution to chronic inflammatory diseases, from that, we hypothesized that this activation could be involved in paracoccidioidomycosis, contributing to chronic inflammation. While inflammasome activation has been demonstrated in experimental models of Paracoccidioides brasiliensis infection, no information is available in patients, leading us to investigate the participation of NLRP3-inflammasome machinery in CF/PCM patients from a Brazilian endemic area. Our findings showed increased priming in mRNA levels of NLRP3 inflammasome genes by monocytes of PCM patients in vitro than healthy controls. Similar intracellular protein expression of NLRP3, CASP-1, ASC, and IL-1β were also observed in freshly isolated monocytes of PCM patients and smoker controls. Increased expression of NLRP3 and ASC was observed in monocytes from PCM patients under hypoxia in comparison with smoker controls. For the first time, we showed that primed monocytes of CF-PCM patients were associated with enhanced expression of components of NLRP3-inflammasome due to smoke. Also, hypoxemia boosted this machinery. These findings reinforce the systemic low-grade inflammation activation observed in PCM during and after treatment.
Keywords: Antifungal therapy; Hypoxia; Inflammasome; Monocytes; Paracoccidioidomycosis; Pulmonary fibrosis